Election Day - Hudak, Heather C. (New York Weigl Publishers Inc., 2007)
Election Day is the day after the first Monday in November each year. People vote for leaders in elections. Each presidential term lasts four years. Presidents can hold office for a maximum of two terms, or eight years.
Elementary
Keywords: Election Day; Elections - United States